Pengaruh Religiusitas, Faktor Sosial Ekonomi, Dan Faktor Teknologi Terhadap Minat Pengggunaan Linkaja Syariah Pada Generasi Z Di Kabupaten Bondowoso : The Influence of Religiosity, Socioeconomic Factors, and Technological Factors on Interest in Using Linkaja Syariah Among Generation Z in Bondowoso Regency - Rachmasari, Alfani; Fadah, Isti; Hanim, Anifatul (IJABAH: Indonesian Journal of Sharia Economics, Business, and Halal Studies, 2023)
This study aims to determine the influence of religion, socio-economic factors, and technological factors on the interest in using Linkaja Syariah in Generation Z in Bondowoso Regency. This type of research uses explanatory research which explains the relationship or influence between independent and dependent variables. This research is a quantitative study with a sample of 80 respondents. The sample is Linkaja Syariah users aged 18-27 years (generation z). The data was obtained by distributing questionnaires, namely in the form of questionnaires directly to the respondents. The data analysis method in this study uses multiple linear analysis. The results of this study were taken based on the regression test. The test results are first, partially religiosity influences interest in use. Second, partially socio-economic factors influence user interest. Third, partially technological factors influence user interest. Fourth, simultaneously religiosity, socio-economic factors, technological factors influence user interest.